2019
DOI: 10.1002/mgg3.678
|View full text |Cite
|
Sign up to set email alerts
|

Targeted fetal cell‐free DNA screening for aneuploidies in 4,594 pregnancies: Single center study

Abstract: Background Next‐generation sequencing (NGS) and discovery of fetal cell‐free DNA (cfDNA) in the maternal circulation render possible prenatal screening for trisomy 21 (Down syndrome), trisomy 18, trisomy 13, and sex chromosome aneuploidies. The approach is called “fetal cfDNA screening” and in contrast to noninvasive conventional serum screening, it provides the identification of 98%–99% of fetuses with Down syndrome. Methods Retrospective analysis of targeted noninvasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
(28 reference statements)
2
5
0
Order By: Relevance
“…Furthermore, our data demonstrated that a well-chosen computational NIPT software employed in combination with appropriate Z-score thresholds can be used at lower sequencing coverages, even at sequencing depths below 5M RPS. This is in line with the current knowledge, as NIPT usage potential at lower coverages (such 2.2M RPS) has been demonstrated previously [ 14 ]. However, at lower sequencing depths (below 5M RPS), the compared computational tools yielded trisomy risks with differing accuracies, reflected by mostly with a systematically increasing numbers of false-positive and false-negative trisomy cases ( Figs 1 and S1 and S2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our data demonstrated that a well-chosen computational NIPT software employed in combination with appropriate Z-score thresholds can be used at lower sequencing coverages, even at sequencing depths below 5M RPS. This is in line with the current knowledge, as NIPT usage potential at lower coverages (such 2.2M RPS) has been demonstrated previously [ 14 ]. However, at lower sequencing depths (below 5M RPS), the compared computational tools yielded trisomy risks with differing accuracies, reflected by mostly with a systematically increasing numbers of false-positive and false-negative trisomy cases ( Figs 1 and S1 and S2 ).…”
Section: Discussionsupporting
confidence: 92%
“…We also observed that a well-chosen computational NIPT software in combination with appropriately applied Z-score thresholds can be used at lower sequencing coverages, even below 5M RPS. This is in line with the current knowledge, also NIPT potential at lower coverages (such 2.2M RPS) has been shown (18). However, at lower sequencing coverages (below 5M RPS), various computational tools infer trisomy risks with a quite different accuracy, mostly with a systematically increasing number of false-positive and false-negative trisomy cases ( Figure 1, Supplementary Figure 1, Supplementary Figure 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, Koc et al . also observed that NIPT test failures (as no result) are often related to the low FF estimation in the case of lower sequencing coverage (18). Also, depending on the software used for FF calculation, FF estimator (17) accuracy can significantly decrease at low sequencing coverages in the case of truly low FF ( Figure 3, Supplementary Figure 6 ).…”
Section: Discussionmentioning
confidence: 92%
“…69 The MiSeq and NextSeq platforms from Illumina have also been successfully used with cffDNA for aneuploidy detection, with a 10.9% failure rate in 3594 MiSeq cases and 8.7% failure rate in 1000 NextSeq cases. 70 Targeted NGS has also been utilized to analyze selected genomic regions of interest for NIPT. 71 In a report by Koumbaris et al, a blind study showed 100% diagnostic sensitivity while being more cost-effective as an NGS-based method for NIPT.…”
Section: Molecular-based Approaches For Detecting and Studying Aneuploidymentioning
confidence: 99%